WORK PROCESSES AND MENTAL HEALTH OF COMMUNITY HEALTH WORKERS: AN INTEGRATIVE REVIEW (REMUNOM, 2026)
Primary Health Care (PHC) is the main gateway to the Unified Health System (SUS) and its central role is the organization of care in the Health Care Network. In this scenario, Community Health Agents (CHA) assume a strategic role by acting as a bridge between health services and the community, strengthening access, bonding, and comprehensiveness of care. This action takes place in territories often marked by social vulnerabilities, which intensifies the risks to the mental health of these workers. In view of this scenario, the present study aimed to identify, in scientific literature, the impacts of work processes and their implications for the mental health of Community Health Agents (CHA). This is an integrative literature review, carried out in the Scielo, Lilacs, Medline and CAPES Journal Portal databases. The searches took place between September and November 2025, using the descriptors "Community Health Agent", "Mental Health" and "Primary Health Care", combined with each other, as well as their English counterparts. Articles published between 2015 and 2025, in Portuguese and English, were included. After applying the eligibility criteria, 13 studies made up the sample. The studies analyzed showed an association between mental illness and work processes in PHC, manifested by common mental disorders, occupational stress, anxiety, depression, and burnout syndrome. Among the main associated factors, work overload, precarious working conditions, low professional appreciation, salary dissatisfaction, exposure to violence in the territories and the fragility of institutional support stood out. Studies with gender perspectives have indicated greater vulnerability of women to psychological distress. These factors had a greater impact in the context of the COVID-19 pandemic, with the persistence of indicators of psychological distress in the post-pandemic period. It is concluded that the work processes in PHC significantly impact the mental health of the CHAs, evidencing illness as a result of organizational and structural determinants of work.